The Influence of Recruitment, Educational Qualifications and Work Placement on the Work Productivity of Employees of the Production Department of Pt. Yangtze Optical Fiber Indonesia - Rismawati, Rismawati; Huda, Miftakul; Mardiana, Riki (Proceeding International Pelita Bangsa, 2023)
In the company's operating system, the potential of human resources is essentially one of the capital and plays a very important role in achieving company goals. The purpose of this study was to determine the effect of recruitment, educational qualifications and job placement on the work productivity of employees of PT Yangtze Optic Fiber Indonesia in the production department. The sample in this study amounted to 60 people. The method used in this research is a quantitative method. Data collection techniques using a questionnaire. With the help of the SPSS 25 application and analysis techniques using validity tests, reliability tests, classic assumption tests, and hypothesis testing consisting of t tests and f tests, as well as tests of the coefficient of determination. The results of this study indicate that partially educational qualifications and job placement have a positive and significant effect on work productivity. While partially recruitment has no positive and significant effect on the work productivity. work productivity of employees of PT Yangtze Optic Fiber Indonesia. Simultaneously, recruitment, educational qualifications and job placement have a positive and significant effect on the work productivity of production employees of PT Yangtze Optic Fiber Indonesia. The coefficient of determination test results show that the work productivity of PT Yangtze Optic Fiber Indonesia employees is influenced by the variables, Recruitment, Educational Qualifications and Job Placement by 64.7%. And the remaining 35.3% is influenced by other variables not examined in this study.